From Workload to Wellness: How Time Availability Shapes Family Healthy Lifestyle in Working Mothers - Yulian Sri Lestari (International Conference on Sustainable Health Promotion, 2025)
This study aims to examine the effect of working mothers’ workload on family healthy lifestyle, with time availability as a mediating variable, particularly in relation to food quality. A quantitative approach was used, employing multiple regression analysis with SPSS. The sample consisted of 250 working mothers who met the following criteria: working at least 30 hours per week, having a spouse and/or child living in the same household. The results revealed that workload had a significant negative effect on time availability (β = -0.268; p = 0.000), and time availability had a significant positive effect on food quality (β = 0.575; p = 0.000). However, the direct effect of workload on food quality was not significant (β = -0.040; p = 0.494). This indicates that workload affects food quality indirectly through limited time availability. The findings emphasize that time management is a key factor in maintaining a healthy family lifestyle, especially among working mothers facing dual roles. Partner support and workplace flexibility play essential roles in helping mothers balance domestic and professional responsibilities effectively